High temperature thermophysical properties of spark plasma sintered tungsten carbide. (April 2022) - Tripathy, H.; Sudha, C.; Paul, V. Thomas; Thirumurugesan, R.; Prasanthi, T.N.; Sundar, R.; Vijayashanthi, N.; Parameswaran, P.; Raju, S.
Abstract: Fast Breeder Test Reactor (FBTR) is a unique Indian fast reactor and irradiation facility for materials testing. As a part of its life extension activities, high density tungsten mono carbide (α-WC) is considered as a candidate material for the lower axial neutron shielding of the grid plate. Spark plasma sintering technique is used to synthesize high density (99.5%) tungsten carbide pellets under optimized conditions without a binder phase and subjected to high temperature thermal property characterization. The dilatational strain, thermal diffusivity as well as the resonance frequency of flexural vibration is measured as a function of temperature and the corresponding values of linear thermal expansion, thermal conductivity and the dynamic Young's modulus are estimated. The measured values are analyzed in combination with quasi-harmonic Debye-Grüneisen model to obtain a comprehensive database on vibrational thermodynamic properties from 0 to 1273 K. The observed Debye temperature for tungsten carbide under ambient conditions is 630 K which gradually decreases to 586 K at 1273 K. The estimated thermal Grüneisen parameter varied in the range of 1.41–1.45. Highlights: Binderless, high density WC has been synthesized using spark plasma sintering. The thermal, elastic and transport properties are measured in the temperature range 298–1273 K The Debye temperature and Grüneisen parameter are calculated as a function of temperature. Quasi-harmonic formalism is adopted to establish thermal properties of WC from 0 to 1273 K. Thermal conductivity for high density WC is reported from 298 to 1487 K.